Differential regulation of intramuscular fat and abdominal fat deposition in chickens - Na Luo; Jingting Shu; Xiaoya Yuan; Yuxi Jin; Huanxian Cui; Guiping Zhao; Jie Wen (BMC Genomics, 2022)
Abstract Background Chicken intramuscular fat (IMF) content is closely related to meat quality and performance, such as tenderness and flavor. Abdominal fat (AF) in chickens is one of the main waste products at slaughter. Excessive AF reduces feed efficiency and carcass quality. Results To analyze the differential deposition of IMF and AF in chickens, gene expression profiles in the breast muscle (BM) and AF tissues of 18 animals were analyzed by differential expression analysis and weighted co-expression network analysis. The results showed that IMF deposition in BM was associated with pyruvate and citric acid metabolism through GAPDH, LDHA, GPX1, GBE1, and other genes. In contrast, AF deposition was related to acetyl CoA and glycerol metabolism through FABP1, ELOVL6, SCD, ADIPOQ, and other genes. Carbohydrate metabolism plays an essential role in IMF deposition, and fatty acid and glycerol metabolism regulate AF deposition. Conclusion This study elucidated the molecular mechanism governing IMF and AF deposition through crucial genes and signaling pathways and provided a theoretical basis for producing high-quality broilers.